Investigating the Effect of Innovation Orientation and Human Capital on Organizational Competitiveness and Performance with the Mediating Role of Supply Chain Integration in the Construction Industry - Javid Bakhshipour Leili; mehrdad Hosseini Shakib (مهندسی و مدیریت ساخت, 2020)
Today, given the complex expectations of customers, organizations find themselves facing customers who want to increase product diversity and better quality; therefore, competition among companies has replaced competition among supply chains. This paper examines the impact of innovation orientation and human capital on competitiveness and performance of organizations, with the mediating role of supply chain integration. A researcher-made questionnaire based on extracted index table is used to collect the required data, content validity ratio and content validity index and Cronbach's alpha are used to determine the validity and reliability of the questionnaire. Data are collected from a survey of 225 employees, managers and suppliers with at least bachelor degree in SET construction co. Given the limited size of the statistical population, the sampling method is the total number method. In this study, partial least squares method using PLS software is used to evaluate structural and measurement models. The results showed that innovative approaches and human capital have positive effects on different aspects of supply chain integration, leading to improved competitive capabilities and firm performance. Organizations that pay particular attention to the position of human capital and innovation are at the forefront of competition.